MP3 PLAYER APPLICATION USING MACROMEDIA FLASH 8 - Zakaria Ansyor; Elly Agustina J. Skom., MMSi (Jurnal Sistem Informasi, 2008)
The background to the development of the technology world at the moment, there arevarious kinds of entertainment facilities, such as MP3 players. In the application ofthis MP3 player can be understood how the Macromedia Flash 8 can make anapplication.In this study, the authors use one example of programming, namely MacromediaFlash 8 is very supportive in making the application.